The Effect Of Pre-Questioning Teaching Technique To The Reading Comprehension Of Grade Ten Students Of Smk Swasta GKPI 1 Pematang Siantar On A Narrative Text - Winda Oktavia Sipangkar; Asima Rohana Sinaga; Novra Melisa P. Hutabarat (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This research aimed to find out the significant effect of the pre-questioning teaching technique on the reading comprehension of Grade Ten students of Smk Swasta Gkpi 1 Pematang Siantar on a narrative text. This research was carried out at SMK Swasta GKPI 1 Pematang Siantar, namely in classes X TKJ A and X TKJ B. The problem statement of this research was the effect of the pre-questioning teaching technique on the reading comprehension of Grade Ten students of SMK Swasta GKPI 1 Pematang Siantar on a narrative text. The researcher used a quantitative method with a quasi-experimental design and used two classes: the experimental class and the control class. The data was collected using a multiple-choice test. The instrument used to collect data was taken from the results of students' pre-test and post-test scores, where the data was calculated manually using MS Excel. The result of this research showed that the average value of the experimental class was 40 in the pre-test and 80,16 score in the post-test. While the average value of the control class was 39,1 score in the pre-test and 65,5 score in the post-test, The results of the students scores on the post-test showed that the use of the pre-questioning teaching technique was very effective in reading narrative text for grade ten students. The t-test calculation showed that the t-test value was higher than the t-table value (3,32>1.670). The null hypothesis (Ho) was rejected. So, it could be concluded that the pre-questioning teaching technique was very significant in developing students reading comprehension, especially in narrative text.